PENGARUH TINGKAT INFLASI DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM (STUDI KASUS PERUSAHAAN TAMBANG YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021) - SRI DEPI; Nersiyanti Nersiyanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of inflation and interest rates on stock prices in mining companies listed on the Indonesian Stock Exchange in 2017-2021. The type of data used in this research is quantitative data in the form of financial reports from 2017-2021, and reports from Bank Indonesia on interest rates and inflation rates. The sample in this study amounted to 36 companies. Data analysis techniques in this study used the classical assumption test, hypothesis testing, multiple linear regression, and the coefficient of determination test. Data processing in this study used the SPSS Software (Statistics Package for the Social Sciences) 20.0 for windows. The results of this study prove that the inflation rate has a negative and significant effect on stock prices, while interest rates do not have a significant effect on stock prices. Simultaneously inflation and interest rates have no effect on stock prices.